1991
DOI: 10.1111/j.1398-9995.1991.tb00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring aliphatic polyamines‐induced histamine release from rat peritoneal mast cells

Abstract: Rat peritoneal mast cells were incubated with different concentrations of naturally occurring aliphatic polyamines, spermine and spermidine, at 0.1-10 mM and the amount of histamine release into the supernatant solutions was measured. The addition of each polyamine to the suspensions of the mast cells caused a histamine release in a dose-dependent manner. The effect of 10 mM spermine and spermidine was as much as that of 0.5 microgram/ml compound 48/80. The histamine release from the cells incubated with each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Polyamines are required for DNA synthesis and cell proliferation (58,59), and for synthesis of proline, the precursor for collagen production (60,61). Consistent with the finding of greater arginase activity in asthma in the current study, serum levels of polyamines are elevated in subjects with asthma and in experimental models of asthma (5,(62)(63)(64)(65). Taken together with previous studies, the present cross-sectional observational study identifies alterations of Arg metabolism in asthma.…”
Section: Discussionsupporting
confidence: 79%
“…Polyamines are required for DNA synthesis and cell proliferation (58,59), and for synthesis of proline, the precursor for collagen production (60,61). Consistent with the finding of greater arginase activity in asthma in the current study, serum levels of polyamines are elevated in subjects with asthma and in experimental models of asthma (5,(62)(63)(64)(65). Taken together with previous studies, the present cross-sectional observational study identifies alterations of Arg metabolism in asthma.…”
Section: Discussionsupporting
confidence: 79%
“…Recent investigations from our laboratory indicate the presence of increased polyphosphoinositide metabolism in activated rat mast cells (5). Moreover, it has been demonstrated that naturally occurring aliphatic polyamines, such as spermine and spermidine, stimulate the phosphorylation of phosphatidylinositol in rat mast cell granules (6) and induce histamine release from rat mast cells (7). Interestingly, spermine at a concentration of 0.1 nimol/1, which in itself could not cause a significant histamine release, showed a tendency to enhance anti-IgEinduced histamine release from mast cells (7).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that naturally occurring aliphatic polyamines, such as spermine and spermidine, stimulate the phosphorylation of phosphatidylinositol in rat mast cell granules (6) and induce histamine release from rat mast cells (7). Interestingly, spermine at a concentration of 0.1 nimol/1, which in itself could not cause a significant histamine release, showed a tendency to enhance anti-IgEinduced histamine release from mast cells (7). These findings, taken together with the widely accepted idea that mast cells are involved mainly in the immediate asthmatic response (3), led us to investigate the levels of peripheral blood polyamines among the same bronchial asthmatic patients with and without attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These polyamines are stored in mast cell secretory granules, appear in the extracellular space through A23187-evoked Ca 2ϩ -dependent processes, and are thought to be involved in biogenesis and homeostasis of secretory granules (4). Furthermore, it has been reported that spermine and spermidine, when applied to mast cells extracellularly, facilitate synthesis and release of histamine from mast cells (7)(8)(9)(10)(11). Spermine and spermidine are also involved in storage and/or release of histamine and serotonin in the mast cell granules (4,12).…”
mentioning
confidence: 99%